An Analysis of Subject-Verb Agreement Errors on Students’ Narrative Writing at the Eleventh Grade SMA Singosari Delitua - Lena Widyawanti Simanjuntak; Septian Sinaga; Sahlan Tampubolon; David Togi Hutahaean; Yanti Kristina Sinaga (UNIVERSITAS PGRI YOGYAKARTA, 2025)
AbstractThis study used qualitative research. The data were analyzed by classifying the types of errors made by the students from students’ paper. The objective of this research were to found out thethe types of error of subject- verb agreement in narrative writing made by students in the eleventh grade and the most dominant error of subject-verb agreement made by students in the eleventh grade of SMA Singosari Delitua. The result showed that are 174 errors made by the XI IPA 1 students in writing narrative text. Misformation error is type of errors which indicate the common error made by students. The number of misformation error are 65 and percentage is 37,3%, followed by omission errors has 55 with percentage is 31,7%, and the third is addition errors has 36 with percentage is 20,7%, the fourth misordering error has 18 with percentage 10,3%. From the explanation above, it shows that the errors of misformation reached the highest frequency, followed by errors of omission, errors of addition and the last misordering in this study. Here are some reasons why the most dominant error of misformation: errors in the use of the wrong form of morpheme or structure. In misformation, students provide and give something, even though it is not true at all. Wrong in forming the construction of a word, phrase, or sentence.Keywords: Error, Narrative, Subject-Verb Agreement, Writing